The 24 December 2018 Eruptive Intrusion at Etna Volcano as Revealed by Multidisciplinary Continuous Deformation Networks (CGPS, Borehole Strainmeters and Tiltmeters). Issue 8 (7th August 2020) - Aloisi, M.; Bonaccorso, A.; Cannavò, F.; Currenti, G.; Gambino, S.
Abstract: We have modeled the fast dike intrusion that started on 24 December 2018 at Mount Etna. The intrusion was accompanied by an intense seismicity swarm that also continued the following day. Since previous studies did not detail the overall chain of events in time during the magma ascent, here we propose a combined analytical and FEM modeling of all available continuous deformation data, focusing on the signals over 2 days (24–25 December) when the continuous deformation networks recorded clear variations directly related to the dike ascent. High‐rate GPS enabled obtaining an early and reliable source model. Borehole instruments (strainmeters and tiltmeters) highlighted clear variations, starting about 1 hr before those recorded by GPS, and moreover, made it possible to improve the dike ascent modeling. In particular, our continuous deformation data clearly revealed not one but two dikes and showed how they evolved in time. We inferred one dike that began propagating in the first kilometer above sea level, continued to rise with a maximum opening of 1.9 m and increased its horizontal dimension until reaching the ground surface. Soon after, continuous deformation networks revealed a new elongated intrusion in the southern flank, matching the south shifted position of the seismic swarm. This second dike, with a thicker opening of 4.9 m, started from a depth of about −3 km (below sea level) but did not reach the ground surface. This proposed multiparametric modeling of continuous deformation data has therefore enabled disentangling the complexity of the real volcanic processes. Key Points: Imaging multidisciplinary continuous deformation data to improve dike ascent modeling Detailed temporal model of the 2018 intrusion at Etna volcano